WRITING ADVERTISEMENT BY MEANS OF GENRE BASED APPROACH FOR TOURISM STUDENTS IN VOCATIONAL FACULTY - Listriyawati, Nyoman Ardiana (Universitas Nahdatul Ulama Surabaya, 2021)
Abstract: Genre Based Approach is known as an approcah which focuses on the function of the text. One skill that needs concerning in this study is writing because students sometimes found difficulties in writing due to lack of knowledge of the function of the text and the structure of the text. Through good knowledge of the text function piror writing, it will help the students write easily. This study attempts to investigate the application of Genre Based Approcah to tourism students for writing advertisement in English Class in Vocational Faculty of Airlangga University. It tries to find information concerning on the lecturer implementing the Genre Based Approach for third semester students, the modification done by the lecturer in the implementation of Genre Based Approach, and the students’ work in response to the implementation of Genre Absed Approcah. Qualitative research is conducted in this study which involves the description, recording, and interpretation of condition that existed at that time. The data collection techniques were derived from observation and interview. Then, the analysis of the data was conducted through categorization, data display and drawing conclusion. The descriptions of the data analysis were presented textually. The results obtained from this study indicate several things. First, the lecturer has already implemented all stages in Genre Based Approcah with some modification that suitable with the students need. Second, the students’ work has already met the purpose of advertisement that is to promote the tourism place and attract the reader to come and visit the place. Keywords: Genre Based Approach, Writing Skill, Students’ work. Abstrak: Genre Based Approach dikenal sebagai pendekatan yang menitikberatkan pada fungsi teks. Salah satu keterampilan yang perlu diperhatikan dalam penelitian ini adalah menulis, karena mahasiswa terkadang mengalami kesulitan dalam menulis karena kurangnya pengetahuan tentang fungsi teks dan struktur teks. Dengan pengetahuan yang baik tentang fungsi teks tulisan sebelum menulis akan membantu mahasiswa dalam menulis dengan mudah. Penelitian ini mencoba untuk mengetahui penerapan Genre Based Approach pada mahasiswa pariwisata untuk menulis iklan di Kelas Bahasa Inggris di Fakultas Vokasi Universitas Airlangga. Penelitian ini bertujuan untuk mencari informasi mengenai dosen yang menerapkan Genre Based Approach untuk mahasiswa semester III, modifikasi yang dilakukan dosen dalam penerapan Genre Based Approach, dan hasil karya mahasiswa dalam menyikapi penerapan Genre Based Approach. Penelitian kualitatif dilakukan dalam penelitian ini yang melibatkan deskripsi, pencatatan, dan interpretasi terhadap kondisi yang ada pada saat itu. Teknik pengumpulan data diperoleh dari observasi dan wawancara. Kemudian, analisis data dilakukan melalui kategorisasi, penyajian data dan penarikan kesimpulan. Deskripsi analisis data disajikan secara tekstual. Hasil yang diperoleh dari penelitian ini menunjukkan beberapa hal. Pertama, dosen sudah menerapkan semua tahapan dalam Genre Based Approach dengan beberapa modifikasi yang sesuai dengan kebutuhan mahasiswa. Kedua, karya siswa sudah memenuhi tujuan periklanan yaitu mempromosikan tempat wisata dan menarik minat pembaca untuk datang dan berkunjung ke tempat tersebut. Kata Kunci : Genre Based Approach, Keterampilan Menulis, Karya Siswa.